The crises and economic cycles - Abed alSamad, Khaldoun (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to identify concept of sessions and modern economic cycles and crises, which are presented in the fluctuations in the direction of macroeconomic variables such as total output and employment, inflation, deflation, unemployment, and frequency which may be regular or irregular. And the study aimed to identify the types and stages of economic cycles and their interpretations, in addition to addressing the economic crisis and determining the types, origins and its relationship with economic cycles. Descriptive study focused on previous studies exploring the correlation between cycles and economic crises. Study concluded internal and external causes of economic crises in-relation to economic cycles, and the modern economic crises has an effort to affect the world, especially in the context of increasing financial integration.